Resurrection in C. Norwid’s Works - Woloszyn, Beata (Respectus Philologicus, 2005)
The article presents the analysis of Norwid’s views on resurrection in the context of eschatological notions of romanticism. The article maintains that Norwid’s concept of man’s final destination is based on theological ideas of Providence, free will, Incarnation, history of salvation and Communion of Saints. The resurrection of man is closely connected with the ultimate aims of history and human culture because the moral growth of man is continued after death in purgatory and is bound up with the idea of compensation and credit. Moral progress in history is achieved by people thanks to different kinds of incarnations, such as work, art, science, and martyrdom. According to Norwid, the term “incarnation” means turning one’s ideas into action on the pattern of incarnated and crucified Christ. The poet managed to incorporate the romantic notion of progress into the biblical history of salvation. As for the notion of a resurrected body, Norwid ignored official post-scholastic theology, which promoted the idea of soul-body dualism. He referred to the biblical idea of the whole person being resurrected and Saint Paul’s notion of the “spiritual body”. A division between soul and body does not make sense to Norwid, who equated the resurrected body with the very essence of the human soul. According to the poet, the resurrected body is the final product of the moral development of a person.